Differences in students' receptiveness towards ICT-enhanced constructivist approach in the Principles of Accounting - Tan, Boon See; Wong, Su Luan; Salleh, Arfah; Hassan, Rashidah; Abu Bakar, Kamariah (Malaysian Educational Technology Association, 2010)
This paper aims to examine the impact of ICT-enhanced constructivist approach in learning Principles of Accounting for different types of secondary school students by exploring the differences of receptiveness between the high and low ICT proficiency learners, and under- and high-achievers. The research was conducted by the Ministry of Education of Malaysia through a ‘try-out’ project conducted at 150 national and technical secondary schools nationwide. A Lesson Plan Guidebook which prescribes the use of ICT through the combination of an educational accounting software with constructivist learning pedagogical approach which emphasises on student-centred learning was provided to guide all accounting teachers who were involved in the project. Receptiveness of students was obtained through a close-ended questionnaire which consists of 34 items measuring eight dimensions including Skill Acquisitions, Teaching Competency, Cooperative Learning, ICT Liking and Utility, ICT Success, Confidence with Technology, Anxiety and Aversion. A total of 1,322 students’ responses were collected and analysed. The overall findings indicate a positive tendency in each dimension of receptiveness of each type of students with moderate levels of anxiety and aversion. There is no significant difference between students with high and low ICT proficiency level for various dimensions. However, the under-achievers demonstrate relatively higher receptiveness for many dimensions.